The relative proportions of water group ions in Saturn's inner magnetosphere: A preliminary study. Issue 8 (12th August 2015) - Wilson, R. J.; Bagenal, F.; Cassidy, T.; Fleshman, B. L.; Crary, F.
Abstract We present a technique to gather ion composition information in the form of relative abundances of the water group ion species in Saturn's inner magnetosphere, utilizing the Cassini Plasma Spectrometer's Straight‐Through Time‐of‐Flight data from two orbits in 2011. We show that between 4.75 and 8 Saturn radii H2O+ ions dominate the water group species, and from 8 to 10 Saturn radii it is OH+ ions that dominate. Our results show that the relative proportion of H3O+ falls fastest with increasing distance, while the proportion of H2O+ decreases slowly. However, O+ and OH+ increase with distance, and O+ is the least dominant ion species out to eight Saturn radii outside of which it is comparable to H3O+. The relative abundance of H2O+ found here matches theoretical work based on Herschel telescopic data very well. These results are compared with other published work, and further improvements to the technique are discussed.